Arrhythmia profile and ablation‐outcome in elderly women with atrial fibrillation undergoing first catheter ablation. Issue 5 (27th March 2021) - Natale, Veronica; Mohanty, Sanghamitra; Trivedi, Chintan; Baqai, Faiz M.; Gallinghouse, Joseph; Della Rocca, Domenico Giovanni; Gianni, Carola; MacDonald, Bryan; Mayedo, Angel; Burkhardt, John David; Gallinghouse, Gerald J.; Al‐Ahmad, Amin; et al.
Abstract: Background: This study evaluated the arrhythmia profile and ablation outcome in women with atrial fibrillation (AF) aged ≥75 years. Methods: A total of 573 consecutive female patients undergoing first AF ablation were classified into group 1: ≥75 years (n = 221) and group 2: < 75 years (n = 352). Isolation of PVs, posterior wall and superior vena cava was performed in all. Non‐PV triggers from other areas were ablated based on operator's discretion. Results: Group 1 had higher prevalence of hypertension (154 (69.7%) vs. 188 (53.4%), p  < .001) and non‐paroxysmal AF (136 (61.5%) vs. 126 (35.8%), p  < .001). Non‐PV triggers were detected in 194 (87.8%) patients from group 1 and 143 (40.6%) from group 2 ( p  < .001) and were ablated in 152 (68.8%) and 114 (32.4%) from group 1 and 2 respectively. Remaining patients (group 1: 69/221 and group 2: 238/352) received no additional ablation. At 4 years, 109 (49.3%) and 185 (52.6%) from group 1 and 2, respectively, were arrhythmia‐free, p  = .69. When stratified by ablation‐strategy, success‐rate was similar across groups in patients receiving non‐PV trigger ablation (96 (63.2%) in group 1 and 76 (66.7%) in group 2, p  = .61), whereas it was significantly lower in group 1 patients not receiving additional ablation compared to those from group 2 (13 (18.8%) vs. 109 (45.8%), p  < .001). Conclusion: Non‐paroxysmal AF was more common in women aged ≥75 years. Furthermore, significantly higher number of non‐PV triggers were detected in elderly women and ablation of those provided similar ablation success as that in women aged < 75 years.